The Effect of Dividend Payout Ratio (DPR) and Dividend Yield on Investors' Perception of Company Profitability (A Case Study of Banking Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period) - Hanifan, Zakie; Sri Wahyuni, Neng Ayu; Agung, Syahrum (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study aims to examine the effect of the Dividend Payout Ratio (DPR) and Dividend Yield on investor perceptions of the profitability of banking companies listed on the Indonesia Stock Exchange for the 2020-2024 period. Dividend policy is a crucial financial decision that reflects the allocation of profits between dividend payments and retained earnings. There is a theoretical controversy between dividend relevance (Gordon-Lintner) and dividend irrelevance (Modigliani-Miller), as well as inconsistent empirical findings regarding the direction of the influence of DPR and DY, which constitute a gap in this research. This study employed a quantitative approach with a causality design and panel data (pooled time-series cross-sectional). The sample was selected using a purposive sampling method based on the following criteria: banking companies listed on the Indonesia Stock Exchange (IDX) throughout 2020-2024, published complete financial reports, consistently distributed dividends, and had complete data available for variable calculations. Data were analyzed using panel data regression with the help of EViews, through the stages of classical assumption testing, model selection (Chow Test, Hausman Test, LM Test), and hypothesis testing (t-test, F-test, coefficient of determination). Investor perception was proxied by Price-to-Book Value (PBV). The results show that DPR has a positive and significant effect on PBV (coefficient 0.028; p=0.001), thus H1 is accepted. Conversely, Dividend Yield has a negative and significant effect on PBV (coefficient -0.185; p=0.003), thus H2 is accepted. These findings confirm signaling theory in emerging markets and indicate that Indonesian banking investors value long-term growth prospects more than short-term dividend yields. This research contributes to the development of dividend policy theory and provides practical implications for banking management in formulating optimal dividend policies by considering domestic investor preferences.